The effect of using greenhouses as a learning medium in horticulture subjects on the skills of grade X agribusiness crops students at SMKN 3 Sidenreng Rappang - Annisa Magfirah; Firman Firman; Suardi Zain; Muhammad Faisal Saade (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effect of using greenhouses as a learning medium on students' skills in the horticulture subject. The type of research used is pre-experimental with a one-group pretest-posttest design. The subjects of this study were all Grade X Agribusiness Crops students at SMKN 3 Sidenreng Rappang, totaling 11 students. Data were obtained through an observation checklist used before and after the treatment. The results showed a significant improvement in students' skills after learning using the greenhouse. The average score before the learning activity was 3.11, which increased to 4.81 after the learning, with a mean difference of 1.70 points. These results indicate that the use of greenhouses as a learning medium is effective in improving students' skills in horticultural cultivation.